El rescate de los juegos tradicionales en las clases de cultura física con los estudiantes del 5to año en la institución Manuel Ignacio monteros Valdivieso periodo 2018-2019. - Benitez Maldonado, Leidy Soledad (2020)
The present investigation titled THE RESCUE OF THE TRADITIONAL GAMES IN THE CLASSES OF PHYSICAL CULTURE IN THE STUDENTS OF THE 5TH YEAR OF THE INSTITUTION "MANUEL IGNACIO MONTEROS VALDIVIESO, LOJA". Being the fundamental problem ¿How to rescue the traditional games in the physical education classes that allows to rescue the traditional culture in the students of the 5th year in the institution "Manuel Ignacio Monteros Valdivieso", whose primary objective is to determine the incidence of traditional games in physical education classes in the students of the 5th year in the institution "Manuel Ignacio Monteros Valdivieso"; Focusing scientifically on two variables; the first the traditional games and the second in the physical culture classes. The research approach is mixed, the type of research is descriptive and its design is quasiexperimental, during the process the scientific, inductive, deductive, statistical, descriptive, analytical, synthetic, and empirical methods were applied. survey and the tests, and instruments such as the questionnaire, pre-test and post-test, with the help of the research elements mentioned in the framework of the previous observation, the following conclusion could be reached: